Some features of organized crime in Kosovo - Beka, Agnesa (Technium Social Sciences Journal, 2020)
Organized crime is considered a serious threat to national and international security. Organized crime in Kosovo is one of the most present and serious forms of criminality. As such it is an evident occurrence especially in states that are in the phase of general transition. This type of crime is appearing more and more every day in new forms of criminal activities, especially in the period of globalization when such activities have advanced and been perfected as a result of technical-technological development. Despite the fact that Kosovo has its vision and interest to prevent and fight organized crime, in Kosovo this type of criminal activity is presented in various forms, such as corruption, drug trafficking, money laundering in real estate and construction, trafficking in human beings, smuggling of migrants, trafficking in weapons and ammunition, etc. Kosovo is not immune from this type of criminality, which is more and more present in all spheres of life and which heavily attacks the legal, economic, political and social order of the state of Kosovo.